Sexual Fantasy and Alternative Universe: A Reception Study of Science Fiction Fans on the Film Dear David - Fauzan Fahmi Baswedan; Latif Ahmad Fauzan (International Journal of Social, Economic, and Business, 2025)
This study explores the reception of science fiction fans toward the portrayal of sexual fantasy in the Alternative Universe (AU) narrative within the Indonesian film Dear David (2023). Using Stuart Hall’s reception analysis, the research aims to understand how audiences interpret the representation of adolescent sexuality, fantasy, and ethical boundaries in digital culture. The study employs a qualitative descriptive method with in-depth interviews involving ten informants identified as science fiction fans. Findings reveal two dominant audience positions negotiation and opposition. The negotiated position views sexual fantasy AU as creative spaces for self-expression, yet emphasizes the need for ethical awareness, privacy, and respect for cultural taboos surrounding sexuality. Conversely, the oppositional position rejects such depictions for their potential to normalize obsessive or inappropriate behavior, particularly when involving real identities without consent. The research also highlights that AU writing functions as an emotional outlet and a coping mechanism, especially among youth seeking freedom from social and familial pressures. However, the commodification of sexual content in AU communities raises further ethical concerns regarding consent, age restrictions, and digital literacy. This study concludes that while AU narratives offer imaginative freedom and psychological escapism, they must be accompanied by ethical sensitivity and media literacy to prevent misinterpretation or harmful normalization. It contributes to audience studies by contextualizing fan reception of sexual fantasy representation in Indonesian media and underscores the importance of family and education in guiding youth self-expression responsibly